DEALING WITH DIFFERENCES IN ACADEMIC STANDARDS AND LEARNING PRACTICES AMONG INTERNATIONAL STUDENTS AS PART OF UNIVERSITY SOCIAL RESPONSIBILITY - Vevere, Velga (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
The focus of the present research is international students’ adaptation in the academic environment. The working hypothesis is that there exists a gap between international students’ perception of the university policy dealing with academic problems and university (international office, student council, and teaching staff) vision of the same issue. The current research employs the following methods: the monographic (literature review) method and series of semi-structured interviews (20 interviews with international students, seven interviews with university lectures who deal with these students on a daily basis), and an in-depth interview with the university vice rector. The research questions are: (1) What are the key factors of the international graduate students’ academic adjustment in Turiba University? (2) What is the role of the university in assuring international students’ academic integration? The results are interpreted qualitatively, using the method of inductive thematic analysis.